2012
DOI: 10.1111/j.1447-0756.2011.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of N‐acetilglucosaminidase and myeloperoxidase activity in patients with endometriosis‐related infertility undergoing intracytoplasmic sperm injection

Abstract: Infertile patients with endometriosis show a distinct pattern of serum and follicular fluid macrophage/neutrophil activation compared to normally ovulating women undergoing ICSI, which may reflect the role of immune and inflammatory alterations in endometriosis-related infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…Myeloperoxidase (MPO), an enzyme restricted to the azurophil granules of neutrophils, has been extensively used as a marker of polymorphonuclear leukocytes accumulation in tissue samples [25][26][27][28][29][30]. N-acetyl-b-D-glucosaminidase (NAG), present in lysosomes, has been employed to detect macrophage accumulation/activation in a variety of animal and human tissues [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Myeloperoxidase (MPO), an enzyme restricted to the azurophil granules of neutrophils, has been extensively used as a marker of polymorphonuclear leukocytes accumulation in tissue samples [25][26][27][28][29][30]. N-acetyl-b-D-glucosaminidase (NAG), present in lysosomes, has been employed to detect macrophage accumulation/activation in a variety of animal and human tissues [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Riley et al [14] found decreased total MPO levels in the peritoneal fluid of stage I endometriosis patients indicating an initially reduced inflammatory neutrophil response, which becomes stronger as the disease progresses. Active MPO levels were found to be decreased in the follicular fluid of endometriosis patients [26]. In menstrual fluid [27] and in peripheral blood [26][27][28], no significant difference was found in active MPO levels between women with and without endometriosis, but no report on total MPO levels was provided.…”
Section: Discussionmentioning
confidence: 97%
“…Other investigators focused on MPO levels in peritoneal [14], follicular [26], or menstrual [27] fluid, measuring only total MPO levels [14] or MPO activity [26,27] (not specific MPO activity). Riley et al [14] found decreased total MPO levels in the peritoneal fluid of stage I endometriosis patients indicating an initially reduced inflammatory neutrophil response, which becomes stronger as the disease progresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations